2022
DOI: 10.3390/ani12243557
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Observer Variability of Quantitative Parameters Used in Contrast-Enhanced Ultrasound of Kidneys of Healthy Cats

Abstract: Contrast-enhanced ultrasound (CEUS) is a non-invasive imaging technique which allows qualitative and quantitative assessment of tissue perfusion. Although CEUS offers numerous advantages, a major challenge remains the variability in tissue perfusion quantification. This study aimed to assess intra- and inter-observer variability for quantification of renal perfusion. Two observers with different levels of expertise performed a quantitative analysis of 36 renal CEUS studies, twice. The CEUS data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These studies have examined normal and pathological aspects, differentiating between inflammatory, degenerative, and neoplastic lesions, while providing discrimination between benign or malignant conditions [ 106 , 119 , 151 ]. Some studies have also been performed on cats [ 86 , 152 , 153 ]. A limited number of studies have explored the application of CEUS in canine andrology, primarily focused on chronic testicular alterations [ 120 ].…”
Section: Contrast-enhanced Ultrasonography (Ceus)mentioning
confidence: 99%
“…These studies have examined normal and pathological aspects, differentiating between inflammatory, degenerative, and neoplastic lesions, while providing discrimination between benign or malignant conditions [ 106 , 119 , 151 ]. Some studies have also been performed on cats [ 86 , 152 , 153 ]. A limited number of studies have explored the application of CEUS in canine andrology, primarily focused on chronic testicular alterations [ 120 ].…”
Section: Contrast-enhanced Ultrasonography (Ceus)mentioning
confidence: 99%
“…In addition, all CEUS scans were obtained with one unit from one vendor and analyzed by using one type of specialised software. CEUS imaging features can be influenced by different imaging protocols, US scanners, and software used, potentially limiting the generalizability of the results [20,23]. Additional prospective studies with longer follow-ups and larger samples are needed to confirm our results.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Additionally, in the present study, the blood velocity indicators (difference in WiR before and after NAC, obtained from ROI 2 normalized and 3 normalized ) significantly differed between the no-recurrence and recurrence groups. This may be because the walls of newly formed vessels inside the tumor are thinner, lacking a muscle layer and easily forming arteriovenous fistulas, which al-lows the contrast agent to diffuse quickly inside the tumor [17,26]. According to Kim et al, rapidly enhancing tumors on MRI are more commonly observed in fast-growing breast cancer and are related to a poor prognosis [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations